An Examination of the Rusbult Investment Model (Marital Satisfaction, Quality of Alternative Relationships, Investment Size, Marital Commitment and Marital Relationship Persistence), on Women on the Verge of Divorce - marzieh nasir; valiolah farzad; m s; f h; m s (پژوهشنامه مددکاری اجتماعی, 2017)
Abstract The aim of the present research is investigating the Rusbult Investment Model (Marital Satisfaction, Quality of Alternative Relationships, Investment Size, Marital Commitment and Marital Relationship Persistence), on women who are on the verge of divorce in the city of Dezful. The sample consisted of 150 women on the verge of divorce who were selected through the availability sampling method. The instruments used consisted of Rusbult’s scale of investment and the Marital Instability Index (MII) by Edward et al. (1987). Pearson correlation coefficients and path analysis Methods were used for data analysis. The results at p<0.05 and p<0.01 showed a significant positive indirect effect of marital satisfaction, and investment size on the marital relationships persistence by mediated marital commitment on women on the verge of divorce, and a significant negative indirect effect of quality of alternative relationships on marital relationships persistence by mediated marital commitment on the women verge of divorce. Keywords: Investment Model, Marital Satisfaction, Quality of Alternative Relationships, Investment Size, Marital Commitment, Marital Relationships Persistence.